Dampak Spillover Penanaman Modal Asing terhadap Produktivitas Industri Manufaktur Medium-High Technology di Indonesia - Harianto, Samuel Kharis; Sari, Dyah Wulan (Fakultas Ekonomi Universitas Samudra, 2021)
This study examines the impact of foreign presence in the Medium-High and High technology manufacturing industry in Indonesia. Using a balanced panel data that consists of 2,397 firms and in the year of 2010-2014, the data was estimated using the multiple regression method. The results show that there is positive spillover when local and foreign firms are in the same industry. Conversely, in different industries, negative spillover occurs in forward linkage when local firms buy the output of foreign firms and no spillover occurs in backward linkage when local firms become the suppliers of foreign firms. The Indonesian government must assure that foreign investment policies must benefit the domestic companies, considering there are some potential losses for domestic enterprises by the presence of foreign direct investment in the domestic market.